Proceedings of the 58th Annual Meeting of the Association for Computational Linguistics 2020
DOI: 10.18653/v1/2020.acl-main.263
|View full text |Cite
|
Sign up to set email alerts
|

It’s Morphin’ Time! Combating Linguistic Discrimination with Inflectional Perturbations

Abstract: Training on only perfect Standard English corpora predisposes pre-trained neural networks to discriminate against minorities from nonstandard linguistic backgrounds (e.g., African American Vernacular English, Colloquial Singapore English, etc.). We perturb the inflectional morphology of words to craft plausible and semantically similar adversarial examples that expose these biases in popular NLP models, e.g., BERT and Transformer, and show that adversarially fine-tuning them for a single epoch significantly im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 41 publications
0
89
0
Order By: Relevance
“…The BERT language model was utilised in two studies in order to create textual adversarial examples: Garg and Ramakrishnan [ 162 ] and Li et al [ 163 ], both of which proposed generating adversarial examples through text perturbations that are based on the BERT masked language model, as part of the original text is masked and alternative text pieces are generated to replace these masks. In their work [ 164 ], Tan et al proposed Morpheus, which is a method for generating textual adversarial examples by greedily perturbing the inflections of the original words in the text to find the inflected forms with the greatest loss increase, only taking into considerations the inflections that belong to the same part of speech as the original word. Unlike most work on textual adversarial examples, Morpheus produces its adversaries by exploiting the morphology of the text.…”
Section: Different Scopes Of Machine Learning Interpretability: a mentioning
confidence: 99%
“…The BERT language model was utilised in two studies in order to create textual adversarial examples: Garg and Ramakrishnan [ 162 ] and Li et al [ 163 ], both of which proposed generating adversarial examples through text perturbations that are based on the BERT masked language model, as part of the original text is masked and alternative text pieces are generated to replace these masks. In their work [ 164 ], Tan et al proposed Morpheus, which is a method for generating textual adversarial examples by greedily perturbing the inflections of the original words in the text to find the inflected forms with the greatest loss increase, only taking into considerations the inflections that belong to the same part of speech as the original word. Unlike most work on textual adversarial examples, Morpheus produces its adversaries by exploiting the morphology of the text.…”
Section: Different Scopes Of Machine Learning Interpretability: a mentioning
confidence: 99%
“…However, this generally involves retraining the model with the adversarial data, which is computationally expensive and time-consuming. Tan et al (2020) showed that simply fine-tuning a trained model for a single epoch on appropriately generated adversarial training data is sufficient to harden the model against inflectional adversaries. Instead of adversarial training, Piktus et al (2019) train word embeddings to be robust to misspellings, while Zhou et al (2019b) propose using a BERT-based model to detect adversaries and recover clean examples.…”
Section: Related Workmentioning
confidence: 99%
“…Large-scale neural models have proven successful at a wide range of natural language processing (NLP) tasks but are susceptible to amplifying discrimination against minority linguistic communities (Hovy and Spruit, 2016;Tan et al, 2020) due to selection bias in the training data and model overamplification (Shah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations